2017
DOI: 10.1177/2041419617700256
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of explosive bare charge equivalent weight

Abstract: Peak overpressure and impulse are the most important parameters in the explosive performance estimation. Available models commonly consider trinitrotoluene explosive as the standard charge. In this article, the trinitrotoluene equivalency factor is studied through verified one-dimensional numerical simulations. The equivalency factors for impulse and overpressure are different and found to be constant with the scaled distance (3-40 m/kg 1/3), which means that a unique value for the equivalency factor is suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
(26 reference statements)
1
6
2
Order By: Relevance
“…Within this observation, the EFs of C4 and COMP-B increases as the scaled distance Z increases, while it was found that the EF for ANFO decreases as Z increases. Our values for the EF for ANFO, C4 and COMP-B in the far-field regime are 0.0%, -2.5% and -2.4% lower than the values obtained by (Grisaro and Edri, 2017), respectively.…”
Section: Resultscontrasting
confidence: 83%
See 4 more Smart Citations
“…Within this observation, the EFs of C4 and COMP-B increases as the scaled distance Z increases, while it was found that the EF for ANFO decreases as Z increases. Our values for the EF for ANFO, C4 and COMP-B in the far-field regime are 0.0%, -2.5% and -2.4% lower than the values obtained by (Grisaro and Edri, 2017), respectively.…”
Section: Resultscontrasting
confidence: 83%
“…Opposed to the EF values derived in previous studies for the far-field (e.g. Grisaro and Edri, 2017), the calculated EF values for the three examined explosives vary with the scaled distance Z, for a given scaled target size z. However, the variations are quite moderate with the scaled distance.…”
Section: Resultscontrasting
confidence: 69%
See 3 more Smart Citations